2020
DOI: 10.3390/jpm10030090
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Psychological Symptoms of Dementia (BPSD): Clinical Characterization and Genetic Correlates in an Italian Alzheimer’s Disease Cohort

Abstract: Background: The occurrence of Behavioral and Psychological Symptoms of Dementia (BPSD) in Alzheimer’s Disease (AD) patients hampers the clinical management and exacerbates the burden for caregivers. The definition of the clinical distribution of BPSD symptoms, and the extent to which symptoms are genetically determined, are still open to debate. Moreover, genetic factors that underline BPSD symptoms still need to be identified. Purpose. To characterize our Italian AD cohort according to specific BPSD symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Besides memory and learning impairments, as well as other cognitive disturbances, 84 AD patients also show “non-cognitive” symptoms, known as behavioral and psychological symptoms of dementia (BPSD). BPSD are heterogeneous group of behaviors, psychiatric symptoms and mood disorders, 85 diagnosed in approximately 90% of AD patients.…”
Section: Treatment Of Behavioral and Psychological Symptoms Of Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…Besides memory and learning impairments, as well as other cognitive disturbances, 84 AD patients also show “non-cognitive” symptoms, known as behavioral and psychological symptoms of dementia (BPSD). BPSD are heterogeneous group of behaviors, psychiatric symptoms and mood disorders, 85 diagnosed in approximately 90% of AD patients.…”
Section: Treatment Of Behavioral and Psychological Symptoms Of Dementiamentioning
confidence: 99%
“…BPSD are heterogeneous group of behaviors, psychiatric symptoms and mood disorders, 85 diagnosed in approximately 90% of AD patients. BPSD encompass symptoms such as sleep disturbances, anxiety, aggression, depression, wandering, delusion, hallucinations, and disinhibition, 84–87 which are clustered as 1) apathy; 2) affective (anxiety, depression); 3) psychosis (paranoia, delusions, hallucinations); and 4) disinhibition (motor hyperactivity, impulsivity, aggression). 84 , 86 More than 50% of AD patients show more than four neuropsychiatric symptoms at the same time.…”
Section: Treatment Of Behavioral and Psychological Symptoms Of Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological testing and NT lack these problems while maintaining comparable reliability to biomarkers testing (Klages et al, 2005 ; García-Herranz et al, 2020 ). Psychological testing focuses on detecting depressions, anxiety, apathy, and other behavioral and psychological symptoms of dementia (Scassellati et al, 2020 ), while neuropsychological testing is capable of measuring cognitive domains, such as memory, executive function, or attention (Hastings et al, 2014 ), and detecting their alterations. Both psychological and neuropsychological testing should be considered when assessing a subject’s cognitive status because behavioral changes can influence NT scores (García-Herranz et al, 2020 ; Wasserman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the molecular mechanisms of this interaction could allow the development of new personalized therapeutic approaches for treating AD [ 13 ]. Focusing on the occurrence of behavioral and psychological symptoms of dementia in AD (BPSD), other authors have found an interesting association between APOE and MTHFR genetic variants and BPSD, expanding the knowledge about the BPSD etiopathogenetic mechanisms, which in turn, leads not only improve the clinical/diagnostic assessment, but also to better definite suitable treatments [ 14 ].…”
mentioning
confidence: 99%